(untitled) (Journal of Universal Science Research, 2025)
Qualitative research methods play a significant role in exploring complex social phenomena by focusing on meanings, experiences, and contextual interpretations. These methods allow researchers to gain deep insights into human behavior, cultural patterns, and social interactions that cannot be fully captured through numerical measures. The flexibility of qualitative approaches supports open-ended inquiry and enables the discovery of new concepts and theories emerging directly from the data. Despite these strengths, qualitative methods also present several limitations.